EVALUASI ALINYEMEN HORIZONTAL JALAN RAYA RUAS JALAN SITUBONDO-BAJULMATI (KABUPATEN BANYUWANGI) STA 0+000 – STA 5+000 - Himawan Ario Wicaksono; Nugroho Utomo; Aulia Dewi Fatikasari (LPPM Universitas Abdurrab, 2025)
The Situbondo City - Bajulmati Road Section (Banyuwangi Regency) is one of the national roads connecting Situbondo City and Banyuwangi Regency. This road section is one of the national roads with a fairly high accident rate given the condition of the road on the hills. The frequent occurrence of traffic accidents on this road section is caused by the topography of the road which has hilly characteristics. The hilly topography causes the Situbondo City - Bajulmati (Banyuwangi Regency) STA 0+000 - STA 5+000 road section to have a road with long inclines and descents that have a risk of brake failure and loss of control of the vehicle on steep and cornering roads. The horizontal alignment evaluation uses the Bina Marga Method in the form of the 2021 Road Geometric Design Guidelines. This guideline is the latest guideline issued by Bina Marga in 2021 to replace the 1997 Road Geometric Planning Procedure. Horizontal alignment evaluation is carried out by analyzing the degree of bend, bend radius, length of the transition curve and type of horizontal bend. From the results of the evaluation of the horizontal alignment of the highway on the Situbondo City - Bajulmati Road section (Banyuwangi Regency), it is known that the calculation of the horizontal alignment using the Bina Marga method results in a horizontal alignment evaluation of 13 Spiral-Circle-Spiral type bends.